A Review of Converters for Green Hydrogen Generation in Consideration of Renewable Energy - Saman Vivanthanarot; Surin Khomfoi; Teeraphon Phophongviwat; Nattapon Somboonpanya; Suwaphit Phongsawat; Woravut Jeanpanitpong (My University, 2024)
Hydrogen is set to revolutionize the future energy landscape with its wide-ranging applications across various sectors. With global decarbonization objectives, water electrolysis provides a sustainable way to produce hydrogen, especially when it is driven by renewable energy sources. This process predominantly utilizes grid electricity, but the growing implementation of renewable energy-powered microgrids presents an attractive alternative for hydrogen production. The produced hydrogen can be used not only for electrical generation within the microgrid but also for local heating and as a fuel for transportation. Power converters are crucial in ensuring stability and reliability in hydrogen production. The paper reviews the power electronics converters required to match the DC and AC voltage source with the needs of electrolyzers. Moreover, this paper explores the technologies of electrolyzers powered by renewable energy sources, with a particular focus on wind turbines and PV.
Keywords: Hybrid Renewable Energy Systems; Hydrogen Storage and Materials; Spacecraft and Cryogenic Technologies